2013
DOI: 10.1159/000350309
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Insulin-Like Growth Factor 1 and Insulin-Like Growth Factor 1 Receptor is Associated with the Favorable Clinicopathologic Parameters in Small Intestinal Carcinomas

Abstract: Objective: The insulin-like growth factor (IGF) system has been known to play a critical role in tumor development and progression in many human cancers. However, the role of the IGF system in small intestinal carcinoma (SIC) has not been studied yet. Methods: We evaluated the expression of IGF1 and IGF1 receptor (IFG1R) in a total of 194 cases of SIC. Results: IGF1 expression was associated with well/moderate differentiation, better survival, lower pT, lower stage and no lymph node metastasis. IGF1R was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…22 In this paper, IFG1R might be a strong candidate as a downstream effector of miR-296-5p function because of its oncogenic property in various cancers, including cervical cancer and small intestinal carcinoma. 23,24 Our data first showed that miR-296-5p directly targeted IFG1R, and IGF1R was an important mediator of circ_0067835 function in CRC cells. However, the direct evidence between the miR-296-5p/IFG1R axis and circ_0067835-mediated CRC development and radiosensitivity in vivo was absent, which was expected to be investigated in further work.…”
Section: Discussionmentioning
confidence: 83%
“…22 In this paper, IFG1R might be a strong candidate as a downstream effector of miR-296-5p function because of its oncogenic property in various cancers, including cervical cancer and small intestinal carcinoma. 23,24 Our data first showed that miR-296-5p directly targeted IFG1R, and IGF1R was an important mediator of circ_0067835 function in CRC cells. However, the direct evidence between the miR-296-5p/IFG1R axis and circ_0067835-mediated CRC development and radiosensitivity in vivo was absent, which was expected to be investigated in further work.…”
Section: Discussionmentioning
confidence: 83%